Structural basis for human PRDM9 action at recombination hot spots - Patel, Anamika; Horton, John R.; Wilson, Geoffrey G.; Zhang, Xing; Cheng, Xiaodong (Genes & development, 2016)
The multidomain zinc finger (ZnF) protein PRDM9 (PRD1–BF1–RIZ1 homologous domain-containing 9) is thought to influence the locations of recombination hot spots during meiosis by sequence-specific DNA binding and trimethylation of histone H3 Lys4. The most common variant of human PRDM9, allele A (hPRDM9 A ), recognizes the consensus sequence 5′-NCCNCCNTNNCCNCN-3′. We cocrystallized ZnF8–12 of hPRDM9 A with an oligonucleotide representing a known hot spot sequence and report the structure here. ZnF12 was not visible, but ZnF8–11, like other ZnF arrays, follows the right-handed twist of the DNA, with the α helices occupying the major groove. Each α helix makes hydrogen-bond (H-bond) contacts with up to four adjacent bases, most of which are purines of the complementary DNA strand. The consensus C:G base pairs H-bond with conserved His or Arg residues in ZnF8, ZnF9, and ZnF11, and the consensus T:A base pair H-bonds with an Asn that replaces His in ZnF10. Most of the variable base pairs (N) also engage in H bonds with the protein. These interactions appear to compensate to some extent for changes from the consensus sequence, implying an adaptability of PRDM9 to sequence variations. We investigated the binding of various alleles of hPRDM9 to different hot spot sequences. Allele C was found to bind a C-specific hot spot with higher affinity than allele A bound A-specific hot spots, perhaps explaining why the former is dominant in A/C heterozygotes. Allele L13 displayed higher affinity for several A-specific sequences, allele L9/L24 displayed lower affinity, and allele L20 displayed an altered sequence preference. These differences can be rationalized structurally and might contribute to the variation observed in the locations and activities of meiotic recombination hot spots.